Multiple Properties of Fibonacci - Like Sequences - Kiran Singh Bais, Sonali Devra, (International Journal of Advanced Science and Technology, 2020)
In this paper, we are using basic identities of Fibonacci and Lucas sequence for calculating k-Fibonacci and k- Lucas sequence and we are generalizing them.